2001
DOI: 10.1002/ptr.994
|View full text |Cite
|
Sign up to set email alerts
|

Antiradical and antilipoperoxidative effects of some plant extracts used by Sri Lankan traditional medical practitioners for cardioprotection

Abstract: Reactive oxygen species (ROS) are implicated in many pathogenic processes including the cardiovascular system. Detoxification of ROS by antioxidants (AO) therefore affords protection against such diseases. There is a growing body of evidence suggesting that antioxidants contribute to cardioprotection. Therefore, nine plants that are components of Ayurvedic formulations used for the therapy of cardiovascular diseases were investigated to determine whether antioxidant activity is one of the mechanisms by which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 13 publications
3
23
0
1
Order By: Relevance
“…The Environmental and Molecular Mutagenesis. DOI 10.1002/em plants Cichorium intybus and Terminalia arjuna that are present in Liv 52 have been reported to possess antioxidant and antilipoperoxidative activities [Gazzani et al, 2000;Gupta et al, 2001;Kim and Yang, 2001;Munasinghe et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…The Environmental and Molecular Mutagenesis. DOI 10.1002/em plants Cichorium intybus and Terminalia arjuna that are present in Liv 52 have been reported to possess antioxidant and antilipoperoxidative activities [Gazzani et al, 2000;Gupta et al, 2001;Kim and Yang, 2001;Munasinghe et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…In Ayurveda, it is used as antihelmentic and in folklore system, it is used in the treatment of asthma, cancer, jaundice, liver disorders, wounds, rheumatism, joint pains, antiallergic agent etc [2]. Extract of nirgudi has been shown various biological activities such as antibacterial [3], antifeedant [4], antifungal [5], antilarval [6], insecticidal [7], pesticidal activity [8], analgesic activity [9], anti-inflammatory activity [10,11], anticonvulsant activity [12], antioxidant activity [13,14] etc. Almost all parts of nirgudi like leaves, roots, bark, fruits, flowers and seeds are used for medicinal purpose in the form of powder decoction, juice, oil, dry extract etc [15].…”
Section: Introductionmentioning
confidence: 99%
“…A new diterpenoid, negundol was reported from the seeds of V. negundo (Zheng et al, 2012). Pharmacologically, the plant has been reported as hepatoprotective (Avadhoot & Rana, 1991), antibacterial (Perumal-Samy et al, 1998), hypnotic (Gupta et al, 1999), antioxidant (Munasinghe et al, 2001), analgesic and antihistaminic (Dharmasiri et al, 2003), anticancer (Diaz et al, 2003), antiandrogenic (Das et al, 2004), and anti-inflammatory (Tandon & Gupta, 2006). Nair and Saraf (2005) investigated the extract of V. negundo in guinea-pig tracheal smooth muscle and found that it inhibits the release of histamine and products of arachidonic acid metabolism, which are responsible for tracheal smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 99%